IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN “TEKS NARASI SEJARAH” UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - H.A Zakariah, Fatmawati; Daroe Iswatiningsih; Riza Ummaroch; Yeni Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the contextual approach in teaching historical narrative texts and to examine its influence on elementary students’ critical thinking skills. The research was conducted at SD Muhammadiyah 2 Kupang involving 23 sixth-grade students using a qualitative case study design. Data were collected through observation, semi-structured interviews, and documentation. The findings indicate that connecting historical content with students’ daily experiences increases their learning interest, active participation, and critical thinking abilities. The teacher acts as a facilitator who encourages idea exploration and discussion, and despite limited learning facilities, students are still able to analyze facts and relate them to local social and cultural values. Overall, the use of a contextual learning approach provides more meaningful learning experiences and contributes to the improvement of students’ critical thinking skills at the elementary level.